National meeting of the DyTAELs in Senegal - Piraux, Marc; Belmin, Raphael; Mbaye, Banna (2024)
The Agroecology Initiative supports local agroecological transitions through Agroecological Living Landscapes (ALL). In Senegal, this initiative is active in the Fatick department through a local dynamic called DYTAEL (Dynamique pour une Transition AgroEcologique locale), which began in 2021. DyTAEL is part of the broader DyTAES platform, established in 2019, aimed at promoting agroecology through awareness, research, advocacy, and policy dialogue. DyTAES involves 80 organizations from arious sectors, including farmers, NGOs, and public authorities. There are currently 11 DyTAELs in Senegal, each at different stages of development. These local initiatives are driven by regional stakeholders and aim to influence agricultural policies towards greater sustainability. A meeting attended by 96 people, was held to evaluate the performance of the DyTAELs. The Initiative funded the event, which allowed participants to present their successes, challenges, and lessons learned. This exchange focused on improving operations and sharing the experience of the Fatick ALL. The results and conclusions from the workshop are documented in a report. Many of the points raised here are taken from the general DyTAES report: RENCONTRE BILAN DES 5 ANS DE LA DYTAES of November 2024.